Insights Into the Research Status of Neuromedin U: A Bibliometric and Visual Analysis From 1987 to 2021 - Qi, Xueping; Liu, Peidong; Wang, Yanjie; Xue, Jinmei; An, Yunfang; Zhao, Changqing (Frontiers in Medicine, 2022)
Neuromedin U (NMU) is a regulatory peptide that is widely distributed throughout the body and performs a variety of physiological functions through its corresponding receptors. In recent years, NMU has become the focus of attention in various fields of research as its diverse and essential functions have gradually been elucidated. However, there have been no bibliometrics studies on the development trend and knowledge structure of NMU research. Therefore, in this study, we used VOSviewer software to statistically analyze scientific data from articles related to NMU to track the developmental footprint of this research field, including relevant countries, institutions, authors, and keywords. We retrieved a total of 338 papers related to NMU, written by 1661 authors from 438 organizations of 41 countries that were published in 332 journals. The first study on NMU was reported by a group in Japan in 1985. Subsequently, nine articles on NMU were published from 1987 to 2006. A small leap in this field could be detected in 2009, with 30 articles published worldwide. Among the various countries in which this research has been performed, Japan and the United States have made the most outstanding contributions. Miyazato M, Kangawa K, and Mori K from the Department of Biochemistry, National Retrain and Cardiovascular Center Research Institute in Japan were the most productive authors who have the highest number of citations. Keyword analysis showed six clusters: central-nervous-system, homeostasis, energy metabolism, cancer, immune inflammation, and food intake. The three most highly cited articles were associated with inflammation. Overall, this study demonstrates the research trends and future directions of NMU, providing an objective description of the contributions in this field along with reference value for future research.